1989
DOI: 10.1073/pnas.86.10.3891
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nerve growth factor biosynthesis by beta-adrenergic receptor activation in astrocytoma cells: a potential role of c-Fos protein.

Abstract: The chain of events that results in increased production of nerve growth factor (NGF) following f8-adrenergic receptor (BAR) stimulation has been investigated in the C6-2B rat astrocytoma cell line. Exposure of these cells to the BAR agonist isoproterenol elicits the following cascade of events: (i) increase of cAMP content; (ii) increase of c-Fos mRNA content; (iii) accumulation of c-Fos protein immunoreactivity in the nucleus; (iv) increase of NGF mRNA content. The increase in c-Fos mRNA and its translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(61 citation statements)
references
References 30 publications
(17 reference statements)
4
54
1
2
Order By: Relevance
“…The characteristic coupling of the ET A receptor to G protein subunits might explain the specificity of ET-1-induced NGF augmentation. In contrast to the present study, a previous study reported that the cAMP-PKA pathway was involved in β-adrenoreceptor-mediated NGF augmentation in astrocytoma cells (30). The finding that ET-1 does not induce NGF augmentation in cardiac fibroblasts suggests that the NGF induction pathway is mediated in a cell type-specific manner.…”
Section: Figurecontrasting
confidence: 99%
“…The characteristic coupling of the ET A receptor to G protein subunits might explain the specificity of ET-1-induced NGF augmentation. In contrast to the present study, a previous study reported that the cAMP-PKA pathway was involved in β-adrenoreceptor-mediated NGF augmentation in astrocytoma cells (30). The finding that ET-1 does not induce NGF augmentation in cardiac fibroblasts suggests that the NGF induction pathway is mediated in a cell type-specific manner.…”
Section: Figurecontrasting
confidence: 99%
“…The brain was removed, and brain areas were dissected on ice, frozen on dry ice, and stored at Ϫ80°C until further processing. NGF mRNA levels in mice were determined by Northern blot analysis as previously described (34,35). In brief, total RNA was extracted and size-fractionated by agarose/formaldehyde gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…In astrocytes, PKC activation was associated with increased NGF, whereas increased cAMP levels did not affect NGF expression (48). In astrocytoma cells, c-fos activation increases NGF and inhibiting c-fos-reduced ␤-adrenergic receptor activation of NGF (49). In glioma cells PKA, PKC, or increased Ca 2ϩ mediates AP-1 (c-fos/c-jun) binding a consensus sequence in the NGF gene (50).…”
Section: Tlr2 Regulates Ngf Via Nf-bmentioning
confidence: 97%